Diversity management in the workplace: beyond compliance - N.S. Gwele (AOSIS, 2009)
Diversity management is not a numbers game. Diversity management is a holistic and strategic intervention aimed at maximizing every individual's potential to contribute towards the realization o f the organization's goals through capitalizing on individual talents and differences within a diverse workforce environment. Managing interpersonal relationships within a diverse workforce environment presents a number of challenges related to changes in the social, legal and economic landscape, individual expectations and values as well as the inevitable change in organizational culture (Chartered Institute of Personnel and Development 2005: 1-7). Whether or not organizations are effective in managing diversity is a function of senior managements' commitment, and the perceived centrality of diversity management by all those who populate the institution's workspace. Above all it should be clear to all employees, irrespective of race, gender, or vocational/professional status, that each and every one of them has something of value to contribute towards the realization of the institution's mission and goals. It is crucial to determine clear and manageable success indicators, focusing not only on compliance with legal obligations to include and/or increase the number of employees from the underrepresented and designated groups, but also on strategic intervention strategies to be used to promote and nurture individual talent and potential toward the realization of both individual aspirations and organizational goals re-quality patient outcomes.